Uma proposta de rating para avaliação dos projetos de investimento celebrados no setor público brasileiro - Terto, Francisco Leandro de Brito (2021)
Based on information from the Fundo de Desenvolvimento Econômico, Científico, Tecnológico e de Inovação (FUNDECI) of Banco do Nordeste do Brasil (BNB) about projects for financing innovation in products and processes of interest to the productive sector in the region, a risk assessment methodology was developed. The current data is related to the covenant signed with public and private institutions in the position 08/25/2020, containing 1348 convenant, celebrated over the resources from the FUNDECI, between 2010 and 2019, a nd the modeling is adequate to the situations of the covenant in a binary way for two possible outcomes: i) closure, which refers to a successful covenant in its execution, or; ii) judicial charge. Binary dependent variable models with Probit and Logit hyp otheses are estimated for the two described situations and the results allow to infer that the time of establishment of the convenanted institution, the counterpart offered by it, and the duration of the agreements determine positively your chance of succe ss (closure), while the value signed in the covenant instrument contributes negatively in this aspect. Based on the sample analyzed, a rating was established for the agreements, based on the probability of closure estimated by the proposed model, noting th at 340 agreements were rated “D”, 343 rated “C”, 329 rated “B” and 336 rated “A”. Furthermore, in the case of the JUDICIAL CHARGE situation, only the counterpart i s known to be statistically significant, contributing negatively to the occurrence of this ad verse scenario. The use of these tools will allow BNB to guide the way in which the policy for approving the projects that are subjected to it is conducted, as wel l as the elaboration of procedures, routines and conducts that aim to increase the success of the signed covenants.